Bunga telur in the Malay culture / Wan Noorli Razali - Razali, Wan Noorli (Academy of Language Studies, 2023)
Bunga telur consists of hard-boiled eggs decorated with flowers or other embellishments or placed in a decorative container or basket given to guests as a memento for attending the wedding ceremony or reception. In the Malay culture, the gifting of eggs signifies fertility between a married couple. Bunga pahar, on the other hand, is a collection of bunga telurs arranged in cone-shaped structure. It has dual functions; one for decorative purposes and the other, presented to elder family members after they have blessed (blessing would include sprinkling of rose water and flower potpourri on the bride and groom) the wedded couples who are seated on a wedding dias during the bersanding ceremony. In the past, preparation of bunga telur/bunga pahar was a communal effort, prepared two days before the reception. Family members, neighbours and friends would normally help to prepare the eggs. Sometimes eggs were gifted by the kampong folks to the host. This act of contribution is called menanam which literally means planting. The host would record the contribution and return the favour when it is their turn to host a wedding later.